A low-cost boron-containing 780MPa grade hot-dip galvanized dual-phase steel and its preparation method

By adopting low-cost boron-containing chemical components and specific process steps, a microstructure of 780MPa-grade hot-dip galvanized duplex steel is formed, which solves the problems of high production costs and difficult production in the existing technology, and achieves low cost and high efficiency production effect.

CN116179941BActive Publication Date: 2025-02-11PANZHIHUA IRON & STEEL RES INST OF PANGANG GROUP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211585263.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-09
Publication Date
2025-02-11
Estimated Expiration
2042-12-09

AI Technical Summary

Technical Problem

The existing 780MPa grade hot-dip galvanized duplex steel has high production costs, and there are problems of production difficulty and inefficiency during casting and cooling speed.

Method used

Using low-cost boron-containing chemical components, including C, Si, Mn, Cr, Nb, Ti and B, the ferrite matrix is ​​formed by smelting, hot rolling, acid rolling and hot-dip galvanizing process steps. and 35 to 50% of island-like and blocky martensite microstructure.

Benefits of technology

It has achieved low-cost production of 780MPa grade hot-dip galvanized duplex steel, which has reduced the amount of alloy addition, improved production efficiency and market competitiveness, and optimized the product structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003991956720000071
    Figure BDA0003991956720000071
  • Figure BDA0003991956720000072
    Figure BDA0003991956720000072
  • Figure BDA0003991956720000073
    Figure BDA0003991956720000073
Patent Text Reader

Abstract

The invention provides a low-cost boron-containing 780MPa grade hot-dip galvanized dual-phase steel and a preparation method thereof. The chemical composition of the invention comprises, by mass percentage, C: 0.10% to 0.15%, Si: 0.10% to 0.40%, Mn: 1.45% to 1.85%, P≤0.015%, S≤0.010%, Als: 0.010% to 0.060%, N≤0.006%, Cr: 0.20% to 0.60%, Nb: 0.01% to 0.05%, Ti: 0.005% to 0.040%, B: 0.001% to 0.0045%, and the remaining elements are Fe and inevitable impurities. The present invention adopts the C-Si-Mn route of Ti+Nb+B composite microalloying, utilizes Ti to fix N element and gives full play to the role of B element in significantly improving hardenability, reduces the amount of alloy addition, and obtains a low-cost boron-containing 780MPa grade hot-dip galvanized duplex steel, which greatly reduces the cost and improves the market competitiveness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cold-rolled strip production, and in particular to a low-cost boron-containing 780MPa grade hot-dip galvanized dual-phase steel and a preparation method thereof. Background Art

[0002] At present, low-carbon, green and sustainable development with the goal of achieving "carbon peak" and "carbon neutrality" has been elevated to an unprecedented level. The automobile industry is a key industry for "carbon emissions". As the weight of the vehicle body is reduced, fuel consumption and emissions will be greatly reduced. Advanced high-strength steel is the fastest-developed automotive material in recent years. Dual-phase steel has become the preferred advanced high-strength steel for automobiles due to its high strength, low yield ratio and good formability. With the continuous improvement of corrosion resistance requirements, the use of hot-dip galvanized duplex steel is increasing. In the face of severe market challenges, the development of low-cost and high-performance products will be conducive to improving market competitiveness. 780MPa-grade hot-dip galvanized duplex steel is the most widely used advanced high-strength steel, and is favored by major steel companies and automobile manufacturers. Through the query of relevant patents, the patents that are relatively similar to the low-cost boron-containing 780MPa-grade hot-dip galvanized duplex steel are as follows:

[0003] CN 109825768 A discloses a 780MPa grade ultra-thin specification hot-dip galvanized dual-phase steel and a preparation method thereof, wherein the chemical composition mass percentage is: C: 0.03% to 0.07%, Si: 0.001% to 0.10%, Mn: 1.00% to 1.80%, P≤0.012%, S≤0.006%, Al: 0.60 to 1.20%, Nb: 0.010 to 0.050%, Ti: 0.010 to 0.050% , Cr: 0.10~0.30%, Mo: 0.20~0.40%, N≤0.004%, Ni≤0.20%, Cu≤0.20%, the rest are Fe and unavoidable impurities; and C-0.003×Si+0.014×Mn-0.040×P-0.222×S+0.023×Ni+0.003×Cu-0.004×Mo≤0.085; Mo+Cr≥0.30. The hot rolling finishing temperature is 820-900°C, and the thickness of the hot rolled plate is 0.6-1.6mm; the average cooling rate of the strip is ≥20°C / s, and the coiling temperature is 550-650°C; the cold rolling reduction rate is controlled at 30%-70%, the annealing temperature is 780-850°C, the holding time is 30-200s, the strip after holding is cooled, the cooling rate is ≥30°C / s, the dew point in the annealing furnace is -15--60°C, the hydrogen content H2 in the furnace is 1-10%, the temperature of the strip entering the zinc pot is 450-500°C, the zinc liquid temperature is 450-470°C, the aluminum content of the zinc liquid is 0.15-0.25%, and the strip is cooled to below 200°C at a cooling rate of ≥15°C / s after leaving the zinc pot. The addition of a high content of Mo (0.20-0.40%) increases the alloy cost, and the high Al content (0.60-1.20%) makes it easy to block the water outlet during casting, which increases the difficulty of production and is not conducive to the smooth progress of production. The cooling rate requirement of the strip after leaving the zinc pot is high (≥15℃ / s), which is not conducive to the development of production.

[0004] CN 109097705A discloses an 800MPa grade cold-rolled hot-dip galvanized dual-phase steel and a production method thereof, wherein the chemical composition mass percentage is: C: 0.05-0.10%, Mn: 1.60-2.30%, Als: 0.010-1.0%, Si: 0.10-0.60%, Nb: 0.010-0.050%, Cr: 0.05-0.30%, Mo: 0.05-0.30%, P≤0.015%, S≤0.010%, N≤0.008%, and the rest is Fe and unavoidable impurities, and the precious metal elements Cr and Mo satisfy the relationship: 0.05≤Cr+Mo≤0.30, and C+Si / 30+Mn / 20≤0.22. The casting overheat degree in the steelmaking process is 15-30℃, the slab furnace temperature in the hot rolling process is 1180-1300℃, the heating time is 150min-300min, the hot rolling final rolling temperature is 850-950℃, when the strip temperature is ≥620℃, the average cooling rate of the strip is ≥15℃ / s, the coiling temperature is 500-620℃, the cold rolling reduction rate is controlled in the range of 40%-70%, the hot dip galvanizing annealing temperature is 760-840℃, the heating rate of the temperature ≤760℃ is ≤5℃ / s, and the heating rate of 760 -840℃ holding time is 60-300s, cooling rate is ≥15℃ / s, dew point in annealing furnace is 0~-40℃, H2 content in furnace is 1-5%, H2O / H2≤1.0, strip entering zinc pot temperature is 440-500℃, zinc liquid temperature is 450-470℃, aluminum content of zinc liquid is 0.15-0.25%, and higher content of Mo (0.05~0.30%), Mn (1.60%-2.30%) and Nb (0.010-0.050%) elements are added, which increases alloy cost.

[0005] CN 109943765 A discloses a 800MPa grade high yield ratio cold-rolled dual-phase steel and a preparation method thereof, wherein the chemical composition mass percentage is: C: 0.08-0.10%, Si: 0.6-0.8%, Mn: 1.8-2.0%, Cr: 0.6-0.8%, Als: 0.03-0.06%, Nb: 0.04-0.06%, P≤0.02%, S≤0.01%, and the balance is Fe and inevitable impurities; the billet or ingot is heated to a temperature range of 1180-1260°C, and the billet or ingot is rolled 5-10 times by a rough rolling mill, the billet or ingot thickness after rough rolling is 30-50mm, and then rolled 5-7 times by a hot continuous rolling mill to the required After the thickness is measured, the steel is coiled into a steel coil within the T1 temperature range, the T1 temperature range is 540-620℃; the cold rolling reduction rate is 50-75%, the cold rolled steel treated by the pickling and cold rolling step is first slowly heated to 170℃, then quickly heated to the T2 temperature range, and kept warm for 90-160s; after cooling to the T3 temperature range at the speed of V1, it is quickly cooled to the T4 temperature range at the cooling speed of V2, and after aging treatment for 350-700s, it is cooled to room temperature; the T2 temperature range is 830-850℃, the T3 temperature range is 640-700℃, and the T4 temperature range is 300-340℃; the V1 value range is 5-7℃ / s, and the V2 value range is 36-60℃ / s. Its high Si content is not conducive to obtaining good surface quality, and it is a cold-rolled continuous annealing product and has a large difference from a hot-dip galvanized product. Summary of the invention

[0006] According to the technical problems raised above, a low-cost boron-containing 780MPa grade hot-dip galvanized dual-phase steel and a preparation method thereof are provided. The technical means adopted by the present invention are as follows:

[0007] A low-cost boron-containing 780MPa grade hot-dip galvanized duplex steel, the chemical composition of which includes, by mass percentage, C: 0.10%-0.15%, Si: 0.10%-0.40%, Mn: 1.45%-1.85%, P≤0.015%, S≤0.010%, Als: 0.010%-0.060%, N≤0.006%, Cr: 0.20%-0.60%, Nb: 0.01%-0.05%, Ti: 0.005%-0.040%, B: 0.001%-0.0045%, and the remaining elements are Fe and unavoidable impurities.

[0008] Preferably, the chemical composition, in percentage by mass, includes: C: 0.11% to 0.14%, Si: 0.20% to 0.35%, Mn: 1.50% to 1.70%, P≤0.012%, S≤0.008%, Als: 0.020% to 0.055%, N≤0.005%, Cr: 0.25% to 0.45%, Nb: 0.015% to 0.030%, Ti: 0.015% to 0.030%, B: 0.002% to 0.003%, and the balance is Fe and unavoidable impurities.

[0009] Furthermore, the microstructure of the dual-phase steel is 50-65% of ferrite matrix (average grain size is 1.2 μm) + 35-50% of island-shaped and block-shaped martensite (average grain size is 0.8 μm).

[0010] Furthermore, the yield strength of the dual-phase steel is 436-492 MPa, the tensile strength is 785-840 MPa, and the elongation A 80 The value is 17.0~22.0%.

[0011] The selection principle and content design reasons of each chemical component of the present invention are as follows:

[0012] As one of the most important components in steel, C determines the strength, plasticity and formability of the steel plate. C is the element with the most obvious solid solution strengthening effect in steel materials. At the same time, the C element can significantly improve the hardenability and avoid pearlite transformation. When the C content is too low, the stability of austenite and the hardenability of martensite in the dual-phase steel decrease, resulting in low strength. The C content in the dual-phase steel is generally not less than 0.02%; when the C content is too high, the plasticity and welding performance of the high-strength steel decrease. Therefore, the C content of the present invention is 0.10% to 0.15%, preferably 0.11% to 0.14%.

[0013] Si plays a significant role in solid solution strengthening in steel, and effectively inhibits the precipitation of carbides and delays pearlite transformation during phase transformation. However, if the Si content is too high, it will significantly increase the deformation resistance during thin gauge rolling, which is not conducive to thin gauge rolling. Silicon can increase the activity of carbon and promote the segregation of carbon in the manganese-rich area. When the two-phase region is heat-insulated, it has the effect of accelerating the diffusion of carbon to austenite, has a significant purification effect on ferrite, improves the purity of ferrite in dual-phase steel, promotes the formation of ferrite, and expands the process window for ferrite formation, thereby obtaining a lower yield ratio. On the other hand, if the silicon content is too high, the brittleness of martensite will be increased, resulting in poor toughness, and the high melting point oxides formed on the surface of the steel plate will affect the surface quality of the steel plate. It is necessary to reduce the silicon content in the steel as much as possible. Therefore, the Si content of the present invention is 0.10% to 0.40%, preferably 0.20% to 0.35%.

[0014] Mn is a good deoxidizer and desulfurizer, and is also a commonly used solid solution strengthening element in steel. Mn can combine with C to form a variety of carbides to play a role in precipitation strengthening, and can also be dissolved in the matrix to enhance the solid solution strengthening effect. Mn is easy to combine with S to form a high melting point compound MnS, thereby eliminating or weakening the hot brittleness caused by FeS and improving the hot working performance of steel. Mn can improve the stability of austenite, shift the C curve to the right, thereby significantly reducing the critical cooling rate of martensite. However, when the Mn content is too high, it is easy to enrich on the surface during the annealing process to form a large amount of manganese, thereby causing the quality of surface galvanizing to decrease. Therefore, in the present invention, the Mn content is 1.45% to 1.85%, preferably 1.50% to 1.70%.

[0015] Al is a common deoxidizer in steel, and can form AlN to pin the grain boundary, thereby refining the grains; in addition, Al has a similar effect to Si, and can inhibit the precipitation of carbides, thereby making the austenite fully carbon-rich. However, when the Al content is too high, the cost and inclusion risk are increased. Therefore, the Al content in the present invention is 0.010% to 0.060%, preferably 0.020% to 0.055%.

[0016] Cr can replace Mn, improve the strength of steel and reduce segregation. Pearlite transformation can also be inhibited. In addition, adding a certain amount of Cr in the present invention can also improve the surface quality. After adding Cr, Cr can react with oxygen and aggregate at the junction of the iron oxide scale and the iron matrix to form a dense (Fe, Cr)2O3 or (Fe, Cr)3O4-rich sharp basement film. The presence of the Fe-Cr-rich sharp basement film hinders the diffusion of oxygen and reduces the formation of iron oxide scale. Therefore, adding Cr can effectively reduce the thickness of the iron oxide scale and the formation of AlN, and improve the adhesion of the iron oxide scale, thereby effectively reducing the pitting defects caused by the pressing of the iron oxide scale. However, when the Cr content is too high, it will lead to increased costs, increased strength and reduced elongation. Therefore, in the present invention, the Cr content is 0.20% to 0.60%, preferably 0.25% to 0.45%.

[0017] Nb exists mainly in the form of NbC in dual-phase steel, which has significant grain refinement and dispersion precipitation strengthening effects. During the hot-dip galvanizing annealing heating process, undissolved NbC particles can pin the ferrite grain boundaries, thereby refining the grains; when the annealing temperature increases to the two-phase region, the NbC dissolution temperature is low, so it is fully dissolved in the matrix, and at the same time, the solid solution C atoms are enriched in the austenite to improve its stability; during the cooling process, the NbC in the ferrite will re-precipitate, thereby producing significant precipitation strengthening. Therefore, the Nb content is 0.01% to 0.05%, preferably 0.015% to 0.030%.

[0018] Ti is very easy to combine with N element to form TiN, thereby fixing N element. At the same time, TiN pins the grain boundary during hot rolling heating to inhibit austenite coarsening, has a good grain refinement effect, and can reduce aging and cold brittleness; in addition, Ti combined with C has a significant precipitation strengthening effect. If the Ti content is too low, the N element cannot be completely fixed, thereby affecting the B element to play a significant role in improving hardenability; if the Ti content is too high, it is easy to produce liquid TiN, thereby deteriorating the plasticity of the material, and in severe cases, it will cause cracking of stamping parts. Therefore, the Ti content is selected to be 0.005% to 0.040%, preferably 0.015% to 0.030%.

[0019] B has the effect of significantly improving the hardenability of austenite and effectively promoting the formation of martensite in dual-phase steel; at the same time, it is very easy to combine with N in the steel to form BN, which plays a role in precipitation strengthening. However, too high a B content will deteriorate the toughness of the steel and increase the manufacturing cost of the steel. Therefore, the B content is selected to be 0.001% to 0.0045%, preferably 0.002% to 0.003%.

[0020] To achieve the purpose of the present invention, the present invention also discloses a technical solution, namely a low-cost boron-containing 780MPa grade hot-dip galvanized dual-phase steel and a preparation method thereof, including the process steps of smelting process, hot rolling process, acid rolling process, and hot-dip galvanizing process. The main specific process steps of the present invention are as follows:

[0021] (a) Smelting process: Smelting according to the chemical composition of low-cost boron-containing 780MPa grade hot-dip galvanized dual-phase steel and casting into slabs;

[0022] (b) Hot rolling process: The slab is subjected to heating, descaling, rough rolling, finish rolling and laminar cooling to obtain a hot rolled coil; the heating temperature is 1200-1250°C, the start temperature of finish rolling is 1000-1080°C, the final temperature of finish rolling is 850-900°C, the coiling temperature is 580-630°C, and "U-type coiling" is adopted (the coiling temperature of the first 80m of the strip head is 610-660°C, and the coiling temperature of the last 100m of the strip tail is 620-670°C). The laminar cooling adopts a sparse cooling method, and the thickness of the hot rolled coil is 2.0-6.0 mm.

[0023] (c) Pickling process: After pickling, the hot rolled coil is cold rolled into cold rolled thin strip steel, the finished product thickness is 0.6 to 2.5 mm, and the total cold rolling reduction rate is 45 to 68%.

[0024] (d) Hot-dip galvanizing process: The cold-rolled thin strip is first heated to 300℃, 700℃ and 780~820℃ at heating rates of 15~20℃ / s, 4~10℃ / s and 0.5~3℃ / s respectively; after being heat-equilibrated for 25~90s, it is slowly cooled to 700~760℃ at a rate of 1~5℃ / s, and then rapidly cooled to 60~120℃ at a rate of 20~45℃ / s. After being heat-equilibrated for 15~40s, the strip is rapidly heated to 450~470℃ by an induction body for balanced galvanizing for 10~40s, and cooled to room temperature at a rate of ≥5℃ / s after exiting the zinc bath. The unit speed is 70-160m / min, and the unit speed gradually decreases with the increase of the cold-rolled thickness of the material. The unit speed decreases by 15m / min for every 0.3mm increase in the thickness of the cold-rolled thin strip. The flattening elongation ranges from 0.30 to 0.65%, and the flattening elongation decreases by 0.05% for every 0.3mm increase in material thickness.

[0025] The present invention adopts the C-Si-Mn route of Ti+Nb+B composite microalloying, utilizes Ti to fix N element and gives full play to the role of B element in significantly improving hardenability, and reduces the amount of alloy added; at the same time, the TiN formed inhibits the coarsening of austenite during the hot rolling heating process, and the addition of Nb element pins the grain boundary to refine the grains during the hot rolling and finishing rolling process. At the same time, the production line advantage is fully utilized, the strip is heated to the two-phase region (ferrite + austenite) and kept warm for a period of time, and then quickly cooled to below the Ms point to form martensite (reducing the amount of alloy added); and the reheating function is used to quickly increase the strip temperature to 460°C for hot-dip galvanizing (improving the corrosion resistance of the strip), because the martensite is tempered to reduce the supersaturation, reduce the hardness difference between ferrite and martensite, improve the hole expansion performance, and obtain a low-cost boron-containing 780MPa grade hot-dip galvanized dual-phase steel. It greatly reduces costs, improves market competitiveness, will produce significant economic benefits, and optimizes product structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0027] Figure 1 This is a scanning electron microscope image of the low-cost boron-containing 780MPa grade hot-dip galvanized dual-phase steel of the present invention.

[0028] Figure 2 It is a schematic diagram of temperature control in the production process of the present invention. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] This embodiment provides two groups of low-cost boron-containing 780MPa grade hot-dip galvanized dual-phase steels, whose chemical compositions are shown in Table 1;

[0032] Table 1 Chemical composition of cold-rolled dual-phase steel in the embodiment (wt.%)

[0033] serial number C Si Mn Cr Nb Ti B P S Als 1 0.13 0.25 1.65 0.28 0.020 0.022 0.0025 0.010 0.003 0.050 2 0.12 0.32 1.60 0.32 0.023 0.031 0.0028 0.008 0.002 0.037

[0034] The above-mentioned method for preparing low-cost boron-containing 780MPa grade hot-dip galvanized dual-phase steel has the following specific process:

[0035] A. Smelting process: After the smelting process, a hot-dip galvanized duplex steel slab with the chemical composition shown in Table 1 is prepared;

[0036] B. Hot rolling process: Figure 2 As shown, the slab is heated, descaled, hot rolled and laminar cooled to obtain a hot rolled coil, and the specific hot rolling process parameters are shown in Table 2;

[0037] Table 2 Main process parameters for hot rolling of low-cost boron-containing 780 MPa grade hot-dip galvanized dual-phase steel in the embodiment

[0038]

[0039] C. Pickling process: After pickling, the hot rolled coil is cold rolled into thin strip steel, wherein the thickness of No. 1 and No. 2 strip steels are 1.2 mm and 1.0 mm respectively, and the cold rolling reduction ratios are 60.0% and 64.3% respectively;

[0040] D. Hot-dip galvanizing annealing process: The cold-rolled thin strip is made into the required product after hot-dip galvanizing annealing. First, the strip is slowly heated to the ambient temperature and kept for a period of time to form a certain ratio of ferrite to austenite. Then, the strip is slowly cooled (to form a small amount of oriented epitaxial ferrite and enhance the stability of the remaining austenite) and quickly cooled (to below the Ms point to transform the supercooled austenite into martensite). Then, the strip is heated to the hot-dip galvanizing temperature (450-470°C) by an induction body for balanced galvanizing (to reduce the supersaturation of martensite, reduce the hardness difference between ferrite and martensite, and improve the hole expansion performance). Finally, it is cooled to room temperature and the strip shape is adjusted by a skin pass mill to increase the yield strength. The specific hot-dip galvanizing annealing process parameters are shown in Table 3:

[0041] Table 3 Main process parameters of hot-dip galvanizing annealing process of low-cost boron-containing 780 MPa grade hot-dip galvanized duplex steel in the embodiment

[0042]

[0043] The microstructures of different types of high-strength steels prepared by the above process are as follows: Figure 1 As shown, the mechanical properties of the above low-cost boron-containing 780MPa grade hot-dip galvanized dual-phase steel are tested according to GB / T228-2010 "Room Temperature Tensile Test Method for Metallic Materials", and are shown in Table 4 below: By comparing the present application with the prior art, it can be found that the present invention reduces the addition of other alloys, reduces the cost, and can meet the requirements

[0044] Table 4 Example - Mechanical properties of low-cost boron-containing 780MPa grade hot-dip galvanized dual-phase steel and comparison with prior art

[0045]

[0046]

[0047] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A low-cost boron-containing 780MPa grade hot-dip galvanized duplex steel, characterized in that: Its chemical composition includes by mass percentage: C: 0.10% ~ 0.15%, Si: 0.10% ~ 0.40%, Mn: 1.45% ~ 1.85%, P ≤ 0.015%, S ≤ 0.010%, Als: 0.010% ~ 0.060%, N ≤ 0.006%, Cr: 0.20% ~ 0.60%, Nb: 0.01% ~ 0.05%, Ti: 0.005% ~ 0.040%, B: 0.001% ~ 0.0045%, and the remaining elements are Fe and unavoidable impurities; During the steel preparation process, the hot-dip galvanizing process is carried out with the following parameters: the cold-rolled thin strip is first heated to 300°C, 700°C and 780-820°C at heating rates of 15-20°C / s, 4-10°C / s and 0.5-3°C / s respectively; after being heat-insulated for 25-90s, it is slowly cooled to 700-760°C at a rate of 1-5°C / s, and then rapidly cooled to 60-120°C at a rate of 20-45°C / s. After being heat-insulated for 15-40s, the strip is rapidly heated by an induction body. It is quickly heated to 450-470℃ for balanced galvanizing for 10-40s. After leaving the zinc pool, it is cooled to room temperature at a speed of ≥5℃ / s. The unit speed is 70-160m / min. As the cold-rolled thickness of the material increases, the unit speed gradually decreases. For every 0.3mm increase in the thickness of the cold-rolled thin strip steel, the unit speed decreases by 15m / min. The flat elongation range is 0.30-0.65%, and the flat elongation decreases by 0.05% for every 0.3mm increase in material thickness.

2. The low-cost boron-containing 780MPa grade hot-dip galvanized dual-phase steel according to claim 1, characterized in that: The chemical composition, by mass percentage, includes: C: 0.11% ~ 0.14%, Si: 0.20% ~ 0.35%, Mn: 1.50% ~ 1.70%, P ≤ 0.012%, S ≤ 0.008%, Als: 0.020% ~ 0.055%, N ≤ 0.005%, Cr: 0.25% ~ 0.45%, Nb: 0.015% ~ 0.030%, Ti: 0.015% ~ 0.030%, B: 0.002% ~ 0.003%, and the balance is Fe and unavoidable impurities.

3. The low-cost boron-containing 780MPa grade hot-dip galvanized dual-phase steel according to claim 1, characterized in that: The microstructure of the dual-phase steel is 50-65% of ferrite matrix + 35-50% of island-shaped and block-shaped martensite.

4. The low-cost boron-containing 780MPa grade hot-dip galvanized dual-phase steel according to claim 1, characterized in that: The yield strength of the dual-phase steel is 436-492MPa, the tensile strength is 785-840MPa, and the elongation is A 80 The value is 17.0~22.0%.

5. The method for producing low-cost boron-containing 780MPa grade hot-dip galvanized dual-phase steel according to any one of claims 1 to 4, characterized in that: The process steps include smelting process, hot rolling process, pickling process and hot-dip galvanizing process. The specific process steps are as follows: (a) Smelting process: Smelting according to the chemical composition of low-cost boron-containing 780MPa grade hot-dip galvanized dual-phase steel and casting into slabs; (b) Hot rolling process: the slab is subjected to heating, descaling, rough rolling, finish rolling and laminar cooling to obtain a hot rolled coil; the heating temperature is 1200-1250°C, the start rolling temperature of the finish rolling is 1000-1080°C, the final rolling temperature of the finish rolling is 850-900°C, the coiling temperature is 580-630°C, U-type coiling is adopted, and the laminar cooling adopts a sparse cooling method. The thickness of the hot rolled coil is 2.0-6.0 mm; (c) Pickling process: After pickling, the hot rolled coil is cold rolled into cold rolled thin strip steel, the finished product thickness is 0.6 to 2.5 mm, and the total cold rolling reduction rate is 45 to 68%.

6. The method according to claim 5, characterized in that During the U-shaped curling process, the coiling temperature of the first 80m of the strip is 610-660℃, and the coiling temperature of the last 100m of the strip is 620-670℃.

Citation Information

Patent Citations

  • 800MPa-grade cold-rolled hot-galvanizing dual-phase steel and production method thereof

    CN109097705A

  • 780MPa ultrathin hot galvanizing dual-phase steel and preparation method thereof

    CN109825768A

  • 800 MPa-grade high-yield-ratio cold-rolled dual-phase steel and preparation method thereof

    CN109943765A

  • Low-carbon-equivalent 1180 MPa-grade hot galvanizing dual-phase steel and production method thereof

    CN112522623A

  • Low-cost 600 MPa-grade hot-dip galvanized complex-phase steel plate and preparation method thereof

    CN113444972A